Endovascular superselective treatment of brain tumors: a new endovascular era? A quick review. (7th February 2014) - Peschillo, Simone; Miscusi, Massimo; Missori, Paolo
Abstract : Background: Intra-arterial therapy for malignant brain tumors, especially high-grade gliomas, has been administered since the 1950s and 1960s when the structure of the blood–brain barrier was first described. However, only with the advent of modern techniques used by endovascular neurosurgeons has it been possible to proceed with the release of chemotherapeutic agents in an ultraselective mode by superselective intra-arterial cerebral infusion (SIACI). Methods: A brief review was performed of all the published works from January 2000 to December 2013 in which the main issue was the superselective endovascular treatment of brain tumors with chemotherapy drugs. Results: Intra-arterial non-selective therapy has been reported to be effective in chemosensitive tumors whereas the results in glioblastoma, at least in the pre-bevacizumab era, have been disappointing. Conclusions: If the SIACI method for delivering bevacizumab after disruption of the blood–brain barrier is proved to be safe and effective in larger phase II and III trials, this paradigm may significantly alter the way chemotherapies are delivered to patients with both diffusely infiltrating low-grade and those with high-grade malignant brainstem gliomas and open a new endovascular era.